Analysis of the knowledge regarding as well as the ability to provide first aid by teachers of secondary schools in the Świętokrzyskie voivodeship - Wydrych, Bartosz; Zięba-Szczepaniak, Paulina Dobrawa; Nowak-Starz, Grażyna (Journal of Education, Health and Sport, 2019)
Introduction: Despite the fact of completing various first aid courses, the course attendees often refrain from providing first and due to fear.Such barrier to provide first aid is usually created by people themselves through thinking that they will further harm the injured rather than help them. From a legal point of view every participant or witness of an accident is obliged to provide first aid. In urgent cases it is necessary to undertake the rescue operation in the first minutes after the accident.The aim of the study:The aim of the research was to examine the level of knowledge about providing first aid among teachers.Materials and methodology: The studies were conducted after obtaining the consent of the School Principals. The diagnostic survey method using the questionnaire technique was utilized in the realisation of this study. The results were elaborated on the basis of the data collected via a questionnaire survey research instrument.Conclusions:Women constituted the strongest group- 80%, men only 20%. 40 people participated in the study, out of which 5% were aged 25 or less and 95% were aged over 25 years. The respondents who completed undergraduate studies constituted 7.5%, whereas 92.5% of people had master’s degrees. The study shows that 62.5% of teachers have been employed for over 10 years, 22.5% have fewer than ten years of practice and only 15% have been employed for a period shorter than 5 years. The majority of teachers, i.e. 85%, have completed first aid courses. Conclusions: The state of the respondents’ knowledge about first aid is satisfactory. A large group of respondents know the current guidelines of the European Resuscitation Council.